Chaos in Learning of Physical Education During The Covid-19 Pandemic Study: Education, Economics and Psychology - Indah Wahyu Meysari; Heny Setyawati; Donny Wira Yudha Kusuma (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The background of the problem as a result of the Covid-19 pandemic has an impact on learning in schools which are not only in the field of education but also economic and psychological problems. The main thing that physical education teachers do in order to be able to do online learning is to always maintain physical and mental health and School Operational Assistance (BOS) funds are expected to be an effective and efficient solution in realizing online learning activities. This study used a qualitative approach with a phenomenological design. The population in this study were 48 teachers of physical education and 10 school treasurers. This study used purposive sampling research with a total of 44 samples teachers of physical education and 10 school treasurers located in Mranggen District with elementary school, junior high school, and senior high school education level. The result of this study in elementary school learning was not effective while in junior and senior high school were quite effective. Psychologically experienced by teachers of physical education, even though there was a sense of worry, it could still be handled properly so that there were no excessive symptoms in the body. Then the School Operational Assistance funds were allocated according to local conditions and situations.